The exogenous model of psychotic experience induced by novel psychoactive substances: A clinical overview - Giovanni Martinotti; Gilberto Di Petta; Tommaso Piro; Eleonora Chillemi; Filippo Maria Ferro (Elsevier, 2024)
The previous two decades have been marked by profound societal transformations, including ongoing developments in the illegal drug market and the emergence of numerous novel psychoactive substances. Nevertheless, a comprehensive understanding of the diverse clinical presentations of psychopathological conditions, particularly within the domain of psychotic symptoms, remains deficient. In this clinical overview, our aim is to provide a detailed analysis of the psychotic manifestations induced by various substances. Exogenous psychoses may present with visual hallucinations, delusional perceptions, and paranoid ideation, frequently accompanied by an ego-dystonic experience that deviate from an individual's customary self-identity. Variations in the presentation of symptoms are also influenced by the specific pharmacological pathways with which the substance interacts. Visual hallucinations characterized by vivid colours and associated with positive or negative emotional experiences are most frequently linked to the serotonergic pathway. Paranoid ideation and auditory hallucinations are primarily associated with the dopaminergic pathways. Dissociative responses, often characterized by feelings of derealization and somatopsychic depersonalization, are typically elicited through glutamatergic pathways. Lastly, the endocannabinoid pathways are associated with anxiety-related psychosis-like states, ideas of reference, grandiose delusions, and paranoid delusions.